PENGARUH MODEL PEMBELAJARAN DAN EKOLITERASI TERHADAP KEMAMPUAN PEMECAHAN MASALAH LINGKUNGAN PESERTA DIDIK - AL Haeriyah Sucia; Agung Purwanto; sucahyanto sucahyanto (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2018)
The purpose of this study is to determine whether there is a model of learning and ekoliteration on the ability to solve environmental problems. This research used experimental method 2 X 2 factorial design. This study was conducted in February - March 2018. The population in this study were all students of class X SMA Negeri 13 Kabupaten Tangerang which amounted to 176 respondents. The sample in this research is 44 respondents randomly simpling. The conclusion showed that there was no significant interaction between learning model and ekoliteration on the ability of problem solving environment of learners; there is one significant problem between learners that is significant between learners whose learning processes use project-based learning and problem-based learning; no one is able to solve the non-significant environmental problems of learners between learners who have high and low ecoliteration; for groups of learners who have high ecoliteration, there are no factors capable of solving environmental problems that are carried out using learning based on project-based learning (A1B1) and problem-based learning (A2B1); for groups of learners who have low ecoliteration, there are no effective differences in environmental problems of learners whose learning process uses project-based learning (A1B2) and problem-based learning (A2B2)